2007
DOI: 10.2172/917975
|View full text |Cite
|
Sign up to set email alerts
|

Kd Values for Agricultural and Surface Soils for Use in Hanford Site Farm, Residential, and River Shoreline Scenarios

Abstract: SummaryThis report provides best estimate K d values and a minimum and maximum range of K d values to be used for agricultural soils and Columbia River bank sediments that exist today or would exist in the future when portions of the Hanford Site are released for farming, residential, and recreational use after the U.S. Department of Energy (DOE) completes clean up of defense waste on the site. The K d values should be used to determine the fate and transport rates of contaminants and their availability for pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Figure 4.8 show observed concentrations over time for , respectively, at the selected monitoring wells, and simulation results for cases in which K d values were varied for the three subunits of the Hanford fm (H1, H2, and H3). The ranges used for the K d values are based on Serne (2007). The hydraulic properties were held constant for these simulation cases at the baseline values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4.8 show observed concentrations over time for , respectively, at the selected monitoring wells, and simulation results for cases in which K d values were varied for the three subunits of the Hanford fm (H1, H2, and H3). The ranges used for the K d values are based on Serne (2007). The hydraulic properties were held constant for these simulation cases at the baseline values.…”
Section: Resultsmentioning
confidence: 99%
“…The lower end of the K d range is typical of what is expected for native Hanford sediments that have very low organic matter content. The upper end may be more representative of values that might develop if the liquid wastes contained dissolved organic matter that sorbs with contaminants and binds with the sediment, or if Hanford sediments were used for future agricultural purposes (Serne 2007). A value of K d = 0 cm 3 /g provides the closest correspondence to measured Tc-99 concentrations for the majority of the selected groundwater monitoring wells.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the low Kd values of Pu in soils and sediments (McCubbin et al, 2004;Serne, 2007), the potential remobilization of small quantities of the actinide is still a concern (Kersting et al, 1999;Santschi and Roberts, 2002;Xu et al, 2014). Previous work by the current authors has demonstrated that negligible Pu present in environmental contaminated soils (from the AWE Aldermaston site) is released into solution (<0.01%) under induced-reducing conditions, suggesting that little Pu is mobilized despite the inferred dissolution of oxide minerals and presence of microorganisms linked to Pu reduction (Kimber et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
“…Nitrate has low sorption characteristics so it flows with the other groundwater (Serne, 2007) but it can readily change chemical form; so nitrate is not considered a conservative constituent in groundwater.…”
Section: Tritium (mentioning
confidence: 99%